Synthesis and characterization of two piperazine containing macrocycles and their transition metal complexes - Pota, Kristof; Johnston, Hannah M.; Madarasi, Enikő; Tircsó, Gyula; Green, Kayla N. (Journal of inorganic biochemistry, 2023)
Rigidification of the ligand scaffolds has been a particular mechanism of interest employed to achieve properties suitable for MRI contrast, catalysis, or other applications of metal complexes. Towards the goal of targeting a 15-anePyN5Pip type ligand, a serendipitous isolation of a 30-anePy2N10Pip2 aza-macrocycle was achieved, instead. X-ray diffraction and determination of pKa events were carried out and compared to 17-anePyN5Pip. Furthermore, the X-ray diffraction of the Cu(II) and Zn(II) complexes of 17-anePyN5Pip was achieved and compared to previous reports of other first-row transition metal derivatives of this ligand. Determination of the log β with both 30-anePy2N10Pip2 and 17-anePyN5Pip with the divalent MnZn metal-ion series was used to demonstrate the impact that the piperazine ring plays compared to other, less rigid macrocycles reported to date. Determination of the log β with of both 30-anePy2N10Pip2 and 17-anePyN5Pip with the divalent MnZn metal-ion series was used to demonstrate the impact that the piperazine ring plays compared to other, less rigid macrocycles reported to date. [Display omitted] •A new 30-membered piperazine containing macrocycle was produced.•X-ray diffraction of the new macrocycle validated the connectivity of the 30-membered macrocycle.•Cu(II) and Zn(II) complexes of a comparable piperazine containing macrocycle were produced for comparison.•log β values for first row transition metal-ions were determined for the new macrocycle.